2021
DOI: 10.1098/rspb.2020.3100
|View full text |Cite
|
Sign up to set email alerts
|

Tree species richness modulates water supply in the local tree neighbourhood: evidence from woodδ13C signatures in a large-scale forest experiment

Abstract: Biodiversity is considered to mitigate the adverse effects of changing precipitation patterns. However, our understanding of how tree diversity at the local neighbourhood scale modulates the water use and leaf physiology of individual trees remains unclear. We made use of a large-scale tree diversity experiment in subtropical China to study eight tree species along an experimentally manipulated gradient of local neighbourhood tree species richness. Twig wood carbon isotope composition ( δ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 53 publications
(89 reference statements)
0
24
3
Order By: Relevance
“…Our outcome represents the first and direct evidence that the neighbourhood complementarity effect increased foliar iWUE (decrease in foliar c i ) through the enhancement of foliar P concentrations and potentially the C assimilation rate. This finding, however, is in contrast with several studies reporting decreasing δ 13 C signatures of trees (increases in foliar c i ) and an improved water supply to focal trees in mixed‐species communities (Jansen et al, 2021; Metz et al, 2016). It should be noted that the response of a target species to neighbourhood diversity and trait dissimilarity may not be representative of the response of the community to plot diversity.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…Our outcome represents the first and direct evidence that the neighbourhood complementarity effect increased foliar iWUE (decrease in foliar c i ) through the enhancement of foliar P concentrations and potentially the C assimilation rate. This finding, however, is in contrast with several studies reporting decreasing δ 13 C signatures of trees (increases in foliar c i ) and an improved water supply to focal trees in mixed‐species communities (Jansen et al, 2021; Metz et al, 2016). It should be noted that the response of a target species to neighbourhood diversity and trait dissimilarity may not be representative of the response of the community to plot diversity.…”
Section: Discussioncontrasting
confidence: 92%
“…The ratio of carbon (C) uptake via assimilation per unit H 2 O loss from transpiration, or water‐use efficiency (WUE), is a key characteristic of ecosystem function that is central to the global cycles of water, energy and C. A few studies have shown that tree diversity enhances soil water availability and tree transpiration through complementarity effect, which arises from niche differentiation or facilitation, and decreases the WUE of individual trees and communities (Chaves et al, 2021; Guevara et al, 2010). The results, however, remain controversial (Grossiord et al, 2014; González de Andrés et al, 2018), and studies on the mechanisms that regulate WUE in forest mixtures are lacking (Jansen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ecophysiological and ecohydrological measurements in mixed forests, such as transpiration or sap flow, are still emerging, and the underlying processes in species mixtures remain elusive (Gebauer et al 2012;Forrester 2015;Lübbe et al 2016;Jansen et al 2021). In general, higher growth rates in mixtures are accompanied by an increased stand water consumption (Forrester et al 2010;Kunert et al 2012;Lübbe et al 2016;Torquato et al 2020), a feature which has also been observed for ecosystems with woody encroachment or invasion (Rascher et al 2011;Caldeira et al 2015;Haberstroh et al 2021).…”
Section: Species Interactions and Drought In Forestsmentioning
confidence: 97%